Maltodextrin quality prepared from spoiled and leftover rice. Issue 1 (October 2020) - Rahman, A; Genisa, J; Zainal,
Abstract: Rice is consumed by most people, especially in Asian countries. Rice consumption resulting left oever rice. Rice also has a low storability and resilience because it is susceptible to microorganisms. It will change to spoiled rice if leave it at room temperature. Both kinds of rice become mull. Hence, it required further processing of spoiled rice and leftover rice. One of the alternatives that can be done is by converting rice into maltodextrin. Maltodextrin is widely used in various industries including food, beverage, chemical and pharmaceutical industries. Similar to starch, maltodextrin is widely used as a thickener as well as an emulsifier. This research was conducted to determine the quality of matodextrin resulting from spoiled rice and leftover rice. Rice converted to maltodextrin by amylase enzyme and dried by using a spray dryer. The treatment is replicated 3 times and the data is statistically analyzed by using T-test. The parameters are water content, ash content, and color. The results showed that the water content of maltodextrin from spoiled rice was 1.6% and the leftover rice was 1.35%. In addition, the ash content resulted 0.37% and 0.48% for spoiled rice and leftover rice, respectively. The color test conducted using a chromameter shows that the brightness is suitable with the expected color of the maltodextrin.